Eliminating gender bias in biomedical research requires fair inclusion of pregnant women and gender diverse people - Mridula Shankar; A. Metin Gülmezoglu; Joshua P. Vogel; Shivaprasad S. Goudar; Annie McDougall; Manjunath S. Somannavar; Sara Rushwan; Yeshita V. Pujar; Umesh Charantimath; Anne Ammerdorffer; Meghan A. Bohren (Communications Medicine)
Abstract Systematic under-representation of pregnant women and gender diverse pregnant people in clinical research has prevented them from benefitting fairly from biomedical advances. The resulting lack of pharmacological safety and efficacy data leads to medicine discontinuation, sub-optimal dosing, and reliance on repurposed therapies. We identify four roadblocks to fair inclusion. First, investment and research are inhibited by protectionist attitudes among research gatekeepers who view pregnancy as a vulnerable state. Second, exclusion ignores human-specific biological variations affecting medication absorption and impacts on the pregnant body. Third, pregnant populations in low-and middle-income countries face a double disadvantage due to gender and location, despite bearing a disproportionate maternal mortality burden. Fourth, perspectives and experiences of pregnant populations are undervalued in clinical intervention design. We propose five actions to optimize fair inclusion: fostering reciprocal partnerships, prioritizing multi-disciplinary research, awareness-raising of the need for pharmaceutical innovation, conducting regulatory analyses, and promoting responsible inclusion over presumptive exclusion.